1934 Va. Acts 137-39, ch. 96, §§ 1-7 - (:unkn) unknown (My University, 1934)
Prohibited possession or use of a machine gun during a violent crime; punishable by death or imprisonment for a minimum of 20 years. Prohibited unlawful possession or use of a machine gun for offensive or aggressive purposes; punishable by imprisonment for a minimum of 10 years. Requires manufacturers to keep a register of machine guns.
Keywords: MACHINE GUN RESTRICTION